Comprehensive RAD51C ovarian cancer variant analysis uncouples homologous recombination and replicative functions - Hayley L. Rein; Yashpal Rawal; Anna L. Palovcak-Lightbourn; Gayatri S. Ganesan; Phoebe S. Parker; Reagan Russell; Kristie E. Darrah; Mohammad Afsar; Meghan R. Sullivan; Sarah R. Hengel; Marc R. Radke; Patricia L. Opresko; et al. (Nature Communications)
Abstract RAD51C is a tumor suppressor gene with over 285 variants of unknown significance (VUS) found in primary ovarian tumors. RAD51C is a paralog of the recombinase RAD51, and it forms complexes with other paralogs to regulate RAD51 activity. We screened 27 ovarian cancer-derived RAD51C VUS to identify those that affect the assembly of functional tetrameric RAD51B-C-D-XRCC2 (BCDX2) complex. With yeast 3-hybrid and biochemical analyses, we identify a mutation cluster of the RAD51C Walker B region affecting protein interactions with other RAD51 paralogs. By further analyzing these variants for homologous recombination (HR), replication fork regression, DNA binding and ATPase activity, and RAD51 filament formation, we identified separation-of-function alleles that uncouple RAD51C distinct enzymatic activities with HR and replication. Thus, our analysis of RAD51C identifies additional VUS with functional defects, which will aid in pathogenicity classification and inform future strategies to treat individuals harboring RAD51C loss-of-function alleles.